Consensus problem of delayed linear multi-agent systems : analysis and design - Liu, Cheng-Lin; Liu, Fei (Professor of control theory) (SpringerBriefs in electrical and computer engineering. Control, automation and robotics., 2017)
"In the context of coupled-coordination control mechanisms, this book focuses on the delay robustness of consensus problems with asynchronously coupled and synchronously coupled consensus algorithms respectively. Moreover, constructive consensus algorithms that tolerate larger communication delays are proposed according to idea of compensation. By providing rigorous theoretical proofs and numerous numerical simulations, it enhances readers' understanding of the consensus coordination control mechanism of multi-agent systems with communication delays"--Provided by publisher.